Serum folate levels among mothers of children with and without cleft lip and palate: A comparative biochemical study - Vidya Ajila; R Gopakumar; B Reema; G Subhas Babu; Shruthi Hegde; K Harini (Wolters Kluwer Medknow Publications, 2014)
Background: Cleft lip and palate is one of the major congenital malformations in the newborn. Folic acid or folate has been postulated to have a protective effect on the occurrence of cleft lip and palate if taken in the periconceptional period. Aims: The aim of this study is to evaluate and compare the serum folate levels of mothers of cleft children with that of mothers with healthy children and women of childbearing age. Materials and Methods: A total of 44 subjects were included in the study of which 28 formed the study group comprising of women who had delivered children with cleft lip and palate and 8 were women who had delivered healthy children and formed Control Group I. Control Group II consisted of 8 women of childbearing age. Serum folate levels were assayed using an automated chemiluminescence assay. Results: We observed no significant difference in the serum folate levels of the study group as compared with the control groups. However, the mean serum folate level in the study group was marginally lower than in Control Group I. Conclusions: Since, in our study, folic acid deficiency could not be demonstrated in the serum of women with cleft children, our results suggest that serum folate levels may not be the only reason for clefting. Furthermore, the range of folate in a population is usually narrow; therefore, a significant difference in the serum folate levels may not be demonstrable.